TANGGUNG JAWAB HUKUM BADAN USAHA JALAN TOL DALAM MENCIPTAKAN KESELAMATAN BERLALU LINTAS PENGGUNA JALAN TOL (STUDI KASUS PECAH BAN TOL JAPEK KM 39+350) - Jenny Alvita; Amad Sudiro (Jurnal Hukum Adigama, 2022)
Damage is a common right found in Indonesia, not to mention found on toll roads. The comfort and safetyof toll road users is the responsibility of the Toll Road Business Entity. The tire burst incident thatoccurred on the Cikarang-Cibatu section of the Jakarta – Cikampek Toll Road KM 39+350 towardsJakarta is one of the forms of negligence of the Operation and Maintenance Sub-Sector of the Toll RoadRegulatory Agency in carrying out the function of monitoring evaluation of the implementation ofplanning and implementation of toll road maintenance construction as referred to in paragraph (1). themandate of the provisions of Article 6 of the PUPR Ministerial Regulation 43/2015. This research is anormative research legal approach and case approach, using a qualitative approach. Due to the accident,the Toll Road Business Entity hereby does not carry out toll road concessions in accordance with thefeasibility standards and the lack of public knowledge causes them to be more sincere about the accidentthat happened to them when compared to demanding compensation from the Toll Road Business Entity.Strict liability & liability based on fault is the responsibility attached to the Toll Road Business Entity.The government needs to make ef orts to increase legal knowledge so that the public knows that thedamage to toll roads is the negligence of the Toll Road Business Entity in carrying out the function ofmanaging toll roads.